A Magyar Pedagógia folyóirat tudománymetriai elemzése: Tendenciák, szerzők, társszerzőségi együttműködés - Nagy, Gyula; Molnár, Gyöngyvér (Magyar Pedagógia, 2017)
The aim of this paper is the complete scientometric analysis of Magyar Pedagógia, which is one of the most significant and oldest Hungarian educational research journals. It was founded in 1892, and it is still issued today. We have digitized and built a well-structured database of all journal articles in our research project, therefore making it possible to analyse them by means of various metadata. Besides analyzing metadata, our aim is to investigate the full text corpus with text mining, which is essential tool of Educational Data Mining (EDM). The first part of the study discusses general scientometric indicators and tendencies such as the amount and length of the articles, the most significant authors’ impacts and backgrounds, the number of citations by authors. How has the ratio of male and female authors changed with time? What is the nationality and institutional background of certain authors? International research has verified that scientific cooperation is growing world-wide (Adams, 2012; Ossenblok, Verleysen, & Engels, 2014; Henriksen, 2016). The second part of the paper focuses on this matter: the collaboration of authors, revealing the co-authorship network of Magyar Pedagógia. The hubs of this network are the most central persons in the collaborative authorship in the field of educational research as regards to the analyzed journal.